The non-uniform composition profile in Ge(Si)/Si(001) quantum dots - Lang, C; Nguyen-Manh, D; Cockayne, D (2004)
The composition profile of a pyramid-shaped Ge(Si)/Si(001) quantum dot has been calculated using a combination of molecular static relaxations and a Monte Carlo process. The strain field and the displacement field of the non-uniformly alloyed quantum dot have been calculated using finite element analysis and compared to the case of a uniform alloying profile. TEM image simulations based on the displacements calculated in the finite element analysis have been performed. It is found that the differences in the contrast between uniformly and non-uniformly alloyed pyramid-shaped quantum dots are not significant.